2019
DOI: 10.1101/641217
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Antibiotic interactions shape short-term evolution of resistance in E. faecalis

Abstract: Antibiotic combinations are increasingly used to combat bacterial infections. Multidrug therapies are a particularly important treatment option for E. faecalis, an opportunistic pathogen that contributes to high-inoculum infections such as infective endocarditis. While numerous synergistic drug combinations for E. faecalis have been identi ed, much less is known about how di erent combinations impact the rate of resistance evolution. In this work, we use high-throughput laboratory evolution experiments to quan… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
28
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
2

Relationship

3
4

Authors

Journals

citations
Cited by 9 publications
(30 citation statements)
references
References 52 publications
(66 reference statements)
2
28
0
Order By: Relevance
“…On the other hand, modulating the drug interaction in the absence of collateral effects will also significantly impact adaptation, with synergistic interactions leading to accelerated adaptation relative to both 1) other types of drug interaction (Figure 4, middle row; compare green curves across row) and 2) single drug adaptation (Figure 4, middle row, left panel). Similar interactiondriven adaptation has been observed in multiple bacterial species (Chait et al, 2007;Michel et al, 2008;Hegreness et al, 2008;Dean et al, 2020).…”
Section: Selection Dynamics Depend On Drug Interaction and Collateralsupporting
confidence: 76%
See 2 more Smart Citations
“…On the other hand, modulating the drug interaction in the absence of collateral effects will also significantly impact adaptation, with synergistic interactions leading to accelerated adaptation relative to both 1) other types of drug interaction (Figure 4, middle row; compare green curves across row) and 2) single drug adaptation (Figure 4, middle row, left panel). Similar interactiondriven adaptation has been observed in multiple bacterial species (Chait et al, 2007;Michel et al, 2008;Hegreness et al, 2008;Dean et al, 2020).…”
Section: Selection Dynamics Depend On Drug Interaction and Collateralsupporting
confidence: 76%
“…When both collateral effects and drug interactions vary, the dynamics can be considerably more complex, and the dominant driver of adaptation can be drug interaction, collateral effects, or a combination of both. Previous studies support this picture, as adaptation has been observed to be driven primarily by drug interactions (Chait et al, 2007;Michel et al, 2008;Hegreness et al, 2008), primarily by collateral effects (Munck et al, 2014;Barbosa et al, 2018), or by combinations of both (Baym et al, 2016b;Barbosa et al, 2018;Dean et al, 2020). Figure 4 shows schematic examples of growth rate adaptation for different types of collateral effects (rows, ranging from cross resistance (top) to collateral sensitivity (bottom)) and drug interactions (columns, ranging from synergy (left) to antagonism (right)).…”
Section: Selection Dynamics Depend On Drug Interaction and Collateralmentioning
confidence: 90%
See 1 more Smart Citation
“…Estimated growth surfaces for ancestral cells as well as all estimated growth rates and IC 50 values are available in ref [66]. rate time series (circles) and both linear and saturating fits to determine mean adaptation rate (lines) for populations grown in conditions A (top 3 rows, red), B (magenta), C (cyan), and D (last 3 rows, blue) for combinations of ceftriaxone (CRO) and ampicillin (AMP).…”
Section: Plos Pathogensmentioning
confidence: 99%
“…Moreover, antibiotic combinations often reduce the rate of resistance evolution during treatment, especially for chronic infections, as highlighted by P . aeruginosa in cystic fibrosis and other bacterial pathogens [ 10 , 17 19 ]. The efficacy of these multitarget treatments is likely explained by a requirement for the co-occurrence of multiple resistance factors for treatment escape.…”
Section: Introductionmentioning
confidence: 99%